2023
DOI: 10.1177/15589250231189812
|View full text |Cite
|
Sign up to set email alerts
|

Review on characteristics of concrete reinforced with nylon fiber

Hisham Jahangir Qureshi,
Jawad Ahmad,
Amer Aljabr
et al.

Abstract: In tension, concrete is often weaker than in compression. To increased the tensile strength of concrete, fibers are added. Nylon fibers (NF) have shown promising results in previous research and tests since their presence has shown significant increases in concrete performance. The purpose of this research is to gather data from previous studies on NF-reinforced concrete (FRC). The key components of this review include concrete flowability, compressive strength, tensile strength, impact strength, rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The reinforcement of polyethylene fiber in concrete significantly affects the workability, especially by increasing the fiber content can lead to more lessening of the workability of the concrete [ [56] , [57] , [58] , [59] , [60] ]. However, conventional concrete is able to cover some difficulties like high flow ability, pass-ability, and stability [ 61 ].…”
Section: Effect Of Wsf On Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reinforcement of polyethylene fiber in concrete significantly affects the workability, especially by increasing the fiber content can lead to more lessening of the workability of the concrete [ [56] , [57] , [58] , [59] , [60] ]. However, conventional concrete is able to cover some difficulties like high flow ability, pass-ability, and stability [ 61 ].…”
Section: Effect Of Wsf On Physical Propertiesmentioning
confidence: 99%
“…The employment of waste synthetic fiber in concrete significantly increases the tensile strength of concrete compared to the control mixture [ [87] , [88] , [89] , [90] ], and tensile strength mainly depends on the content of fiber, while the concrete properties like compressive strength and toughness are not beneficial by the higher proportion of the fiber contents [ 58 , 76 , 87 , 91 , 92 ]. Also, Mita et al [ 57 ] reported that nylon fiber improved the tensile strength of cement composite material at any sampled replacement and water-to-cement ratios.…”
Section: Effect Of Wsf On Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, NF is one of the possible solutions to characterize the fresh and mechanical properties of FRC. The nylon fiber is strong and has better elastic behavior when used in concrete [24]. Apart from concrete, the flexural strength and resistance to cracks initiation of cement mortar could be improved by adding nylon fiber.…”
Section: Introductionmentioning
confidence: 99%